Perlindungan Hak Masyarakat Adat Tengger Mendapatkan Bagi Hasil Pendapatan Wisata Taman Nasional Bromo Tengger Semeru - Wahyu Krisnanto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this research was to find out the contribution of Balai Besar Bromo Tengger Semeru National Park (TN-BTS) from the utilization of tourism in TN-BTS to the Tengger indigenous people as the original owner of the Bromo-Tengger Semeru area as well as to know the solutions that can be done by the Balai Besar TN-BTS to contribute in improving the welfare of Tengger indigenous people living in the national park. This research is qualitative research with an explanative approach, where the interviewed informants were selected using a purposive sampling technique and analyzed with ethnographic analysis techniques. From the results of the research, it is known that Balai Besar TN-BTS has conducted a program of development and utilization of national parks for tourism object activities as well as community empowerment as a form of direct contribution to the improvement of the welfare of Tengger indigenous peoples. However, both development programs have not been able to answer the priority needs of Tengger indigenous peoples. The limitations of authority and main functions owned by Balai Besar TN-BTS become an obstacle for them to be able to contribute to the improvement of the welfare of Tengger indigenous peoples. As a strategic effort so that Balai Besar TN-BTS can contribute directly to the improvement of the welfare of Tengger indigenous people who live in the village within the National Park zone is to share the revenue of National park tourism activities. However, this strategic effort needs to be accompanied by a change in the status of Balai Besar which was originally the Technical Implementation Unit (UPT) of the Minister of Environment and Forestry to the Public Service Agency (BLU).